2020
DOI: 10.1002/uog.21973
|View full text |Cite
|
Sign up to set email alerts
|

Monochorionic twins after in‐vitro fertilization: do they have poorer outcomes?

Abstract: Objective To compare the outcome of monochorionic diamniotic (MCDA) twin pregnancies conceived by in‐vitro fertilization (IVF) or intracytoplasmic sperm injection (ICSI) with that of spontaneously conceived MCDA twins. Methods This was a retrospective cohort study of MCDA twin pregnancies conceived after IVF/ICSI or spontaneously, followed from the first trimester onwards at a single center between January 2002 and September 2018. The primary outcome was survival per fetus from the first trimester until 28 day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(27 citation statements)
references
References 39 publications
0
27
0
Order By: Relevance
“…7,8 So even with a single embryo transfer, the chance of conceiving a monozygotic and mostly monochorionic twin is around 1.5% to 2%, 6,7,9 and their survival is probably lower than that of spontaneously conceived MCDA twins. 10 Apart from fertility treatment, there are no other known risk factors. Spontaneous monozygotic twins happen by chance.…”
Section: How Common Are Mcda Twin Pregnancies and What Causes Them?mentioning
confidence: 99%
“…7,8 So even with a single embryo transfer, the chance of conceiving a monozygotic and mostly monochorionic twin is around 1.5% to 2%, 6,7,9 and their survival is probably lower than that of spontaneously conceived MCDA twins. 10 Apart from fertility treatment, there are no other known risk factors. Spontaneous monozygotic twins happen by chance.…”
Section: How Common Are Mcda Twin Pregnancies and What Causes Them?mentioning
confidence: 99%
“…27 articles could be extracted for full-text analysis. 19 were excluded and eight studies were identified for inclusion in this review ( 15 22 ).…”
Section: Resultsmentioning
confidence: 99%
“…All were retrospective observational studies except for one prospective study. The studies were conducted in various countries around the globe but the majority of studies were on the European population ( 15 , 16 , 19 22 ). Four of the studies ( 15 17 , 22 ) included patients undergoing IVF and ICSI in the assisted conception group.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients explicitly referred in the first trimester for invasive testing or because of an anomaly were not included. The same cohort was included in an earlier study on selective growth restriction and the impact of in vitro fertilization [14,15]. The ultrasound scans were performed according to a well-defined protocol [1,14] by experienced sonographers on Voluson E10/E8/E6/730 (GE Healthcare, Chicago, IL, USA).…”
Section: Study Populationmentioning
confidence: 99%